2019
DOI: 10.1101/595264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of human iPSCs and kidney organoids to develop a cysteamine/mTOR inhibition combination therapy to treat cystinosis

Abstract: Cystinosis is a lysosomal storage disease caused by mutations in CTNS, encoding a cystine transporter, and in its severest form is characterized by cystine accumulation, renal proximal tubule dysfunction and kidney failure. Cystinosis is treated with the cystine-depleting drug cysteamine, however this only slows progression of the disease and there is an urgent need for better treatments. Here, we have generated and characterized the first human induced pluripotent stem cell (iPSC) and kidney organoid models o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…This in line with the study of Rega et al where stimulation of endogenous TFEB activity by genistein was shown to lower cystine levels and rescue the delayed endocytic cargo processing in cystinotic proximal tubule cells 16 . Furthermore, inhibition of mTOR signaling by everolimus was shown to activate autophagy, rescue the number of large lysosomes, and in combination with cysteamine, reverse the cystine/cysteine loading defect in patient-specific and CRISPR-edited cystinotic induced pluripotent stem cells and kidney organoids 48 .…”
Section: Discussionmentioning
confidence: 99%
“…This in line with the study of Rega et al where stimulation of endogenous TFEB activity by genistein was shown to lower cystine levels and rescue the delayed endocytic cargo processing in cystinotic proximal tubule cells 16 . Furthermore, inhibition of mTOR signaling by everolimus was shown to activate autophagy, rescue the number of large lysosomes, and in combination with cysteamine, reverse the cystine/cysteine loading defect in patient-specific and CRISPR-edited cystinotic induced pluripotent stem cells and kidney organoids 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Jamalpoor et al provided evidence that CTNS loss affects lysosomal function by hampering the delivery of newly synthesized lysosomal enzymes from Golgi to lysosomes and/or by inhibiting the maturation of these enzymes within (endo) lysosomal compartments. The latter hypothesis was further confirmed by Festa et al where they have shown the impairment of lysosome proteolysis is a result of defective lysosomal enzymes activation in in vitro and in vivo model of cystinosis [79]. mTOR inhibition has been found to resolve the impaired autophagic flux observed in cystinotic cells.…”
Section: Autophagymentioning
confidence: 72%
“…Similarly, several studies showed that the disruption in tight junction proteins triggers a cascade of events resulting in abnormal cell proliferation, reduced differentiation and repression of apical endocytic receptors, causing epithelial dysfunction in cystinosis [81][82][83]. Mito_TEMPO, a mitochondrial targeted antioxidant, restored the integrity, differentiation and transport function in cystinotic proximal tubular cells as well as in Ctns -/mice [79]. On the other hand, Janssens et al recently showed that blocking the uptake of disulfide-rich plasma proteins, through inhibiting megalin-mediated endocytosis, efficiently prevents accumulation of cystine and delays progression of kidney disease in Ctns -/mice [84].…”
Section: Oxidative Stressmentioning
confidence: 96%
See 2 more Smart Citations